2004
DOI: 10.1093/ecam/neh027
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Endogenous β‐Endorphin by Tetrandrine to Lower Plasma Glucose in Streptozotocin‐Induced Diabetic Rats

Abstract: The role of β-endorphin in the plasma glucose-lowering action of tetrandrine in streptozotocin-induced diabetic rats (STZ-diabetic rats) was investigated. The plasma glucose concentration was assessed by the glucose oxidase method. The enzyme-linked immunosorbent assay was used to determine the plasma level of β-endorphin-like immunoreactivity (BER). The mRNA levels of glucose transporter subtype 4 (GLUT4) in soleus muscle and phosphoenolpyruvate carboxykinase (PEPCK) in the liver of STZ-diabetic rats were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…These results suggested that puerarin exhibits its glucose-lowering action through ␣ 1 -adrenogenic pathway by activating the secretion of ␤-endorphin . Activation of ␣ 1 -adrenoceptors in adrenal medulla increased the release of endogenous ␤-endorphin from adrenal gland in rats (Cheng et al, 2001), which stimulates opioid -receptors to enhance glucose utilisation and reduce hepatic gluconeogenesis, and hence lower plasma glucose level in vivo (Hsu et al, 2004). Interestingly, supplementation of 0.2% kudzu root extract in normal diet for two months reduced arterial pressure, body weight, fasting blood glucose, plasma total cholesterol and insulin levels in both ovariectomised and non-ovariectomised SHRs .…”
Section: Anti-diabetesmentioning
confidence: 99%
“…These results suggested that puerarin exhibits its glucose-lowering action through ␣ 1 -adrenogenic pathway by activating the secretion of ␤-endorphin . Activation of ␣ 1 -adrenoceptors in adrenal medulla increased the release of endogenous ␤-endorphin from adrenal gland in rats (Cheng et al, 2001), which stimulates opioid -receptors to enhance glucose utilisation and reduce hepatic gluconeogenesis, and hence lower plasma glucose level in vivo (Hsu et al, 2004). Interestingly, supplementation of 0.2% kudzu root extract in normal diet for two months reduced arterial pressure, body weight, fasting blood glucose, plasma total cholesterol and insulin levels in both ovariectomised and non-ovariectomised SHRs .…”
Section: Anti-diabetesmentioning
confidence: 99%
“…Drug therapies directed at the estrogen receptor, the progesterone receptor, and human epidermal growth factor 2 receptor (HER2/neu) have resulted in improved clinical outcomes in some breast cancers. However, it is still a formidable challenge to treat those tumors that do not express the aforementioned molecular targets (Sorlie et al, 2001;Sørlie et al, 2003;Schneider et al, could stimulate opioid receptors which increased glucose utilization and/or reduced hepatic gluconeogenesis to lower plasma glucose levels in streptozotocin-diabetic rats (Hsu et al, 2004). In the last few years, great progress has been made assesssing the pharmacological role of Fan in the treatment of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pretreatment of diabetic rats with BU224 inhibited this effect of diosmin ( Figure 4 A). Otherwise, PEPCK is a key enzyme in the regulation of glucose synthesis in the liver [ 17 ]. Consistent to a previous report [ 18 ], hepatic PEPCK expression was increased in diabetic animals.…”
Section: Resultsmentioning
confidence: 99%